Urban mother lode improving urban and ecological balance in a mining community through Riparian Corridor Landscape Development and Mining Musuem in Barangay San Isidro, Angono, Rizal - De Guia, Kristoffer B.; Villajuan, Jose Dan V. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Mining is a source of mineral commodities that all places find important for maintaining and improving their standards of living. Mining is economically important to producing urban cities. The economic opportunities and wealth generated by mining for many producing countries are fundamentals for progressive development. World's megacities are developed by extensive use of minerals that come from mining and quarrying to support their progressive industrialization. This type of urbanization provides privelege to the ecological systems by regulating growth and density within districts, while creating a strategic buffer system along the mining site protecting the urban community. Rizal is bountiful in terms of aggregates and minerals. The existing activity is located in Barangay San Isidro and San Roque since there is an abundance of basalt and rocks aggregates in these areas. The quarrying site was given an additional 161.99 hectares for additional quarrying site by the Department of Environment and Natural Resources (DENR) with a total of 211.99 hectares. There are a lot of opportunities for developing these mining sites, which would help the community around it progress. New Urbanism is a new model that shows how landscape can be the tool for the development of our future ideas. As the world develops, ecological systems become ever more threatened. It achieves balance by focusing on development, while also providing valuable open space an prioritizing on safeguarding the ecological systems. This thesis will explore the possibility of integrating the concept of New Urbanism in a Mining Community through a Riparian Corridor Landscape Development and Mining Musuem in Barangay San Isidro of Angono in the province of Rizal that will improve balance between its urban space and ecology.
includes appendices.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman